2018
DOI: 10.32868/rsj.v1i1.22
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Cigarette Smoking in Saudi Arabia in 2018

Abstract: Background Tobacco smoke is the second leading risk factor for death worldwide. This report aims to determine the recent prevalence of and factors associated with cigarette smoking in Saudi Arabia. Methods Data were pooled from two nationwide cross-sectional surveys conducted in 2018 across the 13 regions of Saudi Arabia. The study targeted Arabic-speaking Saudi residents aged 18 years or older between March and July 2018. Results A total of 7,317 adults across the 13 regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 0 publications
5
54
1
Order By: Relevance
“…The results of this study proved that there is a higher proportion of male smokers with MS than female smokers with MS. A recent study revealed that the prevalence of smoking among female Saudi residents was 3.9% while it was 32.5% in male residents, which means that males are eight times more likely to use tobacco than females. 16 The male predominance is a worldwide finding, as a 2015 global study found that the prevalence of daily tobacco smoking was only 5•4% in women, compared with 25% in men. 10 This gender-related variation could be due to a combination of several factors including the physiological effects of ovarian hormones, and cultural, and behavioral influences.…”
mentioning
confidence: 99%
“…The results of this study proved that there is a higher proportion of male smokers with MS than female smokers with MS. A recent study revealed that the prevalence of smoking among female Saudi residents was 3.9% while it was 32.5% in male residents, which means that males are eight times more likely to use tobacco than females. 16 The male predominance is a worldwide finding, as a 2015 global study found that the prevalence of daily tobacco smoking was only 5•4% in women, compared with 25% in men. 10 This gender-related variation could be due to a combination of several factors including the physiological effects of ovarian hormones, and cultural, and behavioral influences.…”
mentioning
confidence: 99%
“…Although the prevalence of cigarette smoking was relatively higher among males in Saudi Arabia (Algabbani et al, 2018), our study reported a high prevalence of STS among males and female students with a narrow gender gap in consistent with a recent study from the western region of Saudi Arabia (Daradka et al, 2019). A national survey on tobacco use among individuals aged 15 years or older in Saudi Arabia also reported a substantially lower female-male ratio on the prevalence of daily STS compared to that of daily use of all forms of tobacco (Moradi-Lakeh et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…A recent meta-analysis revealed that the pooled estimate of smoking prevalence among college students in Saudi Arabia was 17% (29). Moreover, another contemporary work on the prevalence of cigarette smoking in Saudi Arabia in 2018 found that the prevalence of cigarette smoking was 21.4% of the population (30). In the light of these findings, it can be argued that the prevalence of tobacco use is still high, although the county has run several antismoking initiatives.…”
Section: Discussionmentioning
confidence: 99%